Társadalmi konfliktusokat generáló ökológiai történések a Balaton életében az utóbbi néhány évtizedben – A halfogás csökkenése - Takács, Péter; Turcsányi, Béla; Bíró, Péter (Acta Scientiarum Socialium, 2013)
Social Conflict Generating Ecological Developments in the Life of Lake Balaton in Recent Decades – Decreasing Fish Catches The fisheries sector was the chief utilizer of fish stocks living in the Lake Balaton for centuries, however with recreational use in the forefront the importance of angling has considerably increased in the last sixty years. Due to the diminishing of spawning areas of native fish species, the unadvised stocking of non native ones (silver carp, eel), and the ongoing oligotrophication during the last fifteen years the fish stock size and composition of the lake has changed significantly. Decreasing fish catches and contrasting intrests generate numerous conflicts between fishermen and recreational anglers.
Keywords: fishing; angling; stock size; silver carp; eel